Pyrazinamide-induced Polyarthralgia and Myalgia in a Case of Stable Chronic Kidney Disease - Panda, Bijoy Kumar; Suryawanshi, Vaibhav Rajendra; Bargaje, Medha; L, Sathiyanarayanan (Journal of Pharmacy Practice and Community Medicine)
Pyrazinamide is known to cause hyperuricemia and is followed by gout arthritis. But the fate of this drug in chronic kidney disease (CKD) patients is still not explored in details yet. We report a case of a 65-year-old Asian-Indian woman who was diagnosed with stable CKD 5 years ago and is currently diagnosed with peritoneal tuberculosis with pleural effusion. She was started on antitubercular therapy (ATT). On the 11th day of ATT, she developed a rise in uric acid (from 7.2 mg/dL to 13.1 mg/dL) and creatine kinase levels (from 156 U/L to 887 U/L), followed by polyarthralgia and generalised myalgia on investigation. Her elevated uric acid and creatine kinase levels and polyarthralgia improved on cessation of pyrazinamide, but improvement in her myalgia and muscle weakness was postponed. Pyrazinamide plasma 2 hr levels post dose was performed suspecting polyarthralgia and myalgia as an adverse drug reaction and estimated to be 59 μg/ml (normal range: 20-50 μg/ml). Subjective and objective assessments along with pyrazinamide plasma levels may be an indicative evidence of the adverse reaction as the estimated plasma concentration at 2 hr was higher than the normal range.
Keywords: Pyrazinamide; Polyarthralgia; Myalgia; Stable chronic kidney disease; Plasma levels